Avaliação do potencial bacterívoro de três espécies de cladocera de ocorrência tropical e subtropical - Hayashi, Luciana Hitomi (Universidade Federal de São Carlos, 2012)
Cladocerans occupy an important position in freshwater food webs, acting like a bacteria consumer; being relatively non-selective filter feeders they can exert a strong impact on reducing microbial population. This study aimed to analyze the microbial community structure and evaluate the grazing potential in different life stages of three species of cladoceran socurring in tropical and subtropical climate (Ceriodaphnia silvestrii, Ceriodaphnia cornuta and Daphnia gessneri), using a microscopic study of their filter structures and quantifying the grazing rates, the latter experiments were performed in vitro and in situ using fluorescently labeled bacteria (FLB). The in situ experiments were performed in a predominantly mesotrophic subtropical environment (Lobo-Broa Reservoir, Brazil) on two sampling points with different trophic degrees.In parallel, physical, chemical and biological water variables were also evaluated. The bacterial densities and biomass were similar to those found in freshwater environments. For the morphotypes, there was a dominance of coccobacilli and cocci (78.5% of total). In thein vitro experiments, the lowest values found for individual ingestion rates (IIR) and removal (RR) were respectively 1,1 x 105 Bact.ind -1 h-1 and 0,1 mL.ind -1 h-1 in primiparous C. silvestrii, and the highest values were, respectively, 4,4 x 105 Bact.ind -1 h-1 e 0,4 mL.ind-1 h-1, observed in adult D. gessneri. Neonate sof all species showed relatively high ingestionand removal rates. During the in situ experiments, C.silvestrii, had the highest individual ingestion rates (IIR) 27, 7 x 104 bact ind-1 h-1. In populational terms, the studied daphnids distinguished themselves by consuming large amounts of bacteria in the rainy season. The daphnids grazing for this environment may have contributed to induce changes in the structure of bacterial communities, such as increasing the size and amount of bacterial filaments. Therefore, we noted that the bottom-up control had greater importance during the dry season and the top-down control larges timportance in the rainy season; the availability of resources and predationare also importantin the regulation of bacterial abundancein the Lobo reservoir. The studied species showed a sufficiently narrow mesh network to retain bacteria, the largest average distance between setulaewas found in primiparous C.cornuta (0.39μm), and the smallest in neonate D.gessneri (0.11μm). Although the three species have thinmeshes, the changes in its meshes occur differently for each species.
Keywords: Ecologia; Cladocera; Bacterivoria; Bactérias; Cérdula; FLB; Grazing; Grazing; Bactéria; Cladocera; Setulae; FLB; CIENCIAS BIOLOGICAS::ECOLOGIA